High efficiency perovskite solar cells using DC sputtered compact TiO2 electron transport layer - Hayali Ahmed (EDP Sciences, 2021)
High conductivity and transparency of the electron-transporting layer (ETL) is essential to achieve high efficiency perovskite solar cells (PvSCs). Generally, titanium dioxide (TiO2) has been extensively utilized as an ETL in PvSCs. Both surface roughness and uniformity of the compact-TiO2 (C-TiO2) can influence the efficiency of the PvSC. This work investigates the optimization of the direct current (DC) sputtering power and the ratio of argon (Ar) to oxygen (O2) plasma to achieve high quality ETL films. The effect of changing the DC sputtering power on the C-TiO2 films and subsequently on the overall efficiency was studied. The electrical and optical properties of the C-TiO2 layer were characterized for various DC powers and different ratios of Ar to O2 plasma. It was found that the optimum preparation conditions for the C-TiO2 films were obtained when the DC power was set at 200 W and a flow rate of 6 sccm Ar and 12 sccm O2. A power conversion efficiency (PCE) of 15.3% in forward sweep and 16.7% in reverse sweep were achieved under sunlight simulator of 100 mW/cm2. These results indicate that significant improvement in the efficiency can be achieved, by optimizing the C-TiO2 layer.